2009
DOI: 10.1074/jbc.m807800200
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sphingomyelinase Deficiency Prevents Diet-induced Hepatic Triacylglycerol Accumulation and Hyperglycemia in Mice

Abstract: Acid sphingomyelinase plays important roles in ceramide homeostasis, which has been proposed to be linked to insulin resistance. To test this association in vivo, acid sphingomyelinase deletion (asm ؊/؊ ) was transferred to mice lacking the low density lipoprotein receptor (ldlr ؊/؊ ), and then offsprings were placed on control or modified (enriched in saturated fat and cholesterol) diets for 10 weeks. The modified diet caused hypercholesterolemia in all genotypes; however, in contrast to asm ؉/؉ /ldlr ؊/؊ , t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 35 publications
7
94
1
Order By: Relevance
“…1A) (22). A metabolic interaction between sphingolipid and TAG synthesis has been inferred from previous studies in mice with simultaneous deletions of the acid sphingomyelinase and LDL receptor genes (23). In this case, the absence of acid sphingomyelinase was believed to cause a decrease in the rate of sphingomyelin synthesis, resulting in less DAG and TAG accumulation in liver, together with lower serum lipoprotein levels.…”
Section: Discussionmentioning
confidence: 85%
“…1A) (22). A metabolic interaction between sphingolipid and TAG synthesis has been inferred from previous studies in mice with simultaneous deletions of the acid sphingomyelinase and LDL receptor genes (23). In this case, the absence of acid sphingomyelinase was believed to cause a decrease in the rate of sphingomyelin synthesis, resulting in less DAG and TAG accumulation in liver, together with lower serum lipoprotein levels.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, it has been shown that genetic loss of acid sphingomyelinase can prevent diet-induced obesity, hyperglycaemia and insulin resistance in mice lacking the LDL receptor (Ldlr −/− ), which are prone to metabolic disease when placed on highfat diets [82]. Furthermore, a recent study by Bioni et al demonstrated that treatment of mice with the acidic sphingomyelinase inhibitor amitriptyline attenuates highfat diet-induced elevations in plasma ceramide and improves insulin sensitivity [78].…”
Section: Influence Of Caveolae In Mediating the Effects Of Ceramidementioning
confidence: 99%
“…The mechanism by which this occurs is apparently not through an enhancement in lipogenesis and de novo triglyceride synthesis coupled to insulin resistance and hyperglycemia as is often reported in mice fed high fat diets (34,35). Instead, the current data indicate that the presence of cholesteryl ester is able to limit the mobilization of triglycerides from the liver, perhaps through the relative substrate flexibility previously reported in some neutral lipid-esterifying enzymes (32,33), such that the presence of CE interferes with TG hydrolysis and mobilization from cytoplasmic lipid droplets independent of lipogenesis.…”
Section: Discussionmentioning
confidence: 99%